Total Utility & Marginal Utility - GEHANI, LUBNA (Faculty of Business Administration, 2019)
It is an algebraic expression which allows the ranking of consumption quantities according to satisfaction levels.
Keywords: It is the level of satisfaction obtained from consuming a specific quantity of goods and services.